Research advances in replication-deficient viral vector vaccines - Wang, Junna; Cui, Jin; Li, Guoxin; Yu, Lingxue (Frontiers in Veterinary Science, 2025)
In recent years, replication-deficient viral vector vaccines have attracted much attention in the field of vaccine research and development due to their high safety and immunogenicity. These vaccines use genetic modifications to engineer viral vectors that make them unable to replicate but effective in expressing recombinant proteins and induce immune responses. Currently, replication-deficient adenovirus vectors and poxvirus vectors are widely used in vaccine R&D for a variety of infectious diseases in humans and animals, including AIDS, hepatitis B, pseudorabies, avian influenza, infectious bronchitis in poultry, and foot-and-mouth disease. Replication-deficient viral vaccines have been shown to effectively induce neutralizing antibodies and cellular immune responses, thereby providing effective immune protection. Future development of genetic engineering technology and continuous in-depth research on viral vectors should lead to replication-deficient viral vector platforms that have an essential role in preventing and controlling existing and emerging infectious diseases.